Liquidity constraints, risk premia, and themacroeconomic effects of liquidity shocks - Ivan Jaccard (European Central Bank (ECB), 2013)
We study the transmission of liquidity shocks in a dynamic general equilibrium model where firms and households are subject to liquidity risk. The provision of liquidity services is undertaken by financial intermediaries that allocate the stock of liquid asset between the different sectors of the economy. We find that the macroeconomic effects of liquidity shocks are considerably larger in the model economy that generates a realistic equity premium. Liquidity constraints amplify business cycle volatility and have nonlinear effects on risk premia. Our empirical analysis suggests that the Great Recession was primarily caused by liquidity factors.
Keywords: E44; E51; E32; 330; asset pricing; Bayesian estimation; Great Recession